2020
DOI: 10.1016/j.msksp.2020.102193
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for musculoskeletal physiotherapy

Abstract: Introduction: Musculoskeletal conditions are a leading cause of global morbidity. Access to traditional in-person healthcare can be difficult for some under usual conditions and has become a ubiquitous barrier throughout the COVID-19 pandemic. Telehealth, defined as the 'delivery of healthcare at a distance using information and communication technology' is a solution to many access barriers and has been rapidly adopted by many healthcare professions throughout the crisis. While significant advancements in tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
186
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(211 citation statements)
references
References 52 publications
5
186
1
6
Order By: Relevance
“…Using virtual communication methods, telehealth supports remote access to care for musculoskeletal assessments while maintaining social distancing. 64 Physiotherapists are an important member of the multidisciplinary team to help optimize function, movement, and quality of life for people affected by cancer. 65 Physiotherapy using telerehabilitation instead of conventional face-to-face care could be a lasting alternative to treat people diagnosed with cancer in their home environment after hospital discharge, but additional research is needed.…”
Section: Physiotherapymentioning
confidence: 99%
“…Using virtual communication methods, telehealth supports remote access to care for musculoskeletal assessments while maintaining social distancing. 64 Physiotherapists are an important member of the multidisciplinary team to help optimize function, movement, and quality of life for people affected by cancer. 65 Physiotherapy using telerehabilitation instead of conventional face-to-face care could be a lasting alternative to treat people diagnosed with cancer in their home environment after hospital discharge, but additional research is needed.…”
Section: Physiotherapymentioning
confidence: 99%
“…Within the literature, the advantages and disadvantages of remote consultations and meetings, have been reported from the perspecive of the patient, their family and the service ( Table 2 ), and the environmental and technological practicalities of setting up a service have been reported elsewhere ( Cottrell and Russell, 2020 ; Gilbert et al, 2020 ; Greenhalgh et al, 2018 ; NHS, 2019 ; NHSX, 2020 ; Wherton et al, 2020 ). [Please insert Table 2 near here].…”
Section: Introductionmentioning
confidence: 99%
“…When assessing an MDA's functionality, the clinician will want to assess the MDA's ability to not only improve subjective pain scores, but also to improve objectively quantifiable measures of disability function. The MDAs with highest likelihood of yielding clinical benefit are those whose efficacy on objective measures have been established in peer-reviewed studies [39]. For example, two smaller randomized controlled trials demonstrated efficacy of MDAs with respect to improving both knee and back pain and disability function [40,41].…”
Section: Critically Assessing Musculoskeletal Digital Appsmentioning
confidence: 99%